2019
DOI: 10.1007/s11245-019-09639-4
|View full text |Cite
|
Sign up to set email alerts
|

Searching for Deep Disagreement in Logic: The Case of Dialetheism

Abstract: According to Fogelin's account of deep disagreements, disputes caused by a clash in framework propositions are necessarily rationally irresolvable. Fogelin's thesis is a claim about real-life, and not purely hypothetical, arguments: there are such disagreements, and they are incapable of rational resolution. Surprisingly then, few attempts have been made to find such disputes in order to test Fogelin's thesis. This paper aims to rectify that failure. Firstly, it clarifies Fogelin's concept of deep disagreement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
0
4
0
1
Order By: Relevance
“…We find advocates of competing logics debating with one another not only over the comparative strengths and weaknesses of their candidates but also over the validity of important logical laws, such as modus ponens (Martin and Hjortland 2021). While for advocates of a practice-based approach this clash with logical practice spells a devastating blow to constitutivism, the constitutivists themselves seem content to admit that those who challenge the logical laws putatively constitutive of rational thought cannot be providing rational considerations (Martin 2021b), even if these challenges are taken seriously by their peers. 9 Much as with PSP and PMP, it's likely that other interdisciplinary methods, such as results from cognitive science, will be useful to PLP when investigating certain questions, including the theoretical and aesthetic virtues logicians prize within systems.…”
Section: The Methodology Of Plpmentioning
confidence: 91%
See 1 more Smart Citation
“…We find advocates of competing logics debating with one another not only over the comparative strengths and weaknesses of their candidates but also over the validity of important logical laws, such as modus ponens (Martin and Hjortland 2021). While for advocates of a practice-based approach this clash with logical practice spells a devastating blow to constitutivism, the constitutivists themselves seem content to admit that those who challenge the logical laws putatively constitutive of rational thought cannot be providing rational considerations (Martin 2021b), even if these challenges are taken seriously by their peers. 9 Much as with PSP and PMP, it's likely that other interdisciplinary methods, such as results from cognitive science, will be useful to PLP when investigating certain questions, including the theoretical and aesthetic virtues logicians prize within systems.…”
Section: The Methodology Of Plpmentioning
confidence: 91%
“…Given that various such competing logics are still advocated in the literature, some (Resnik 1999) have concluded that the persistent disagreement between candidate theories in the field is evidence that logic is more akin to ethics than to the sciences. This, however, neglects the significant ways in which logicians as participants in the debates agree, such as on how logics should be evaluated (relative to a purpose), the relative strengths and weaknesses of the various competing theories, and what would constitute sufficient evidence for the resolution of the debate (Martin 2021b) What results is a picture of theory evaluation and debate more similar to the sciences than to ethics (Martin and Hjortland 2021). 7 PLP's positive proposal is to address these shortcomings of traditional philosophy of logic through a combination of re-orientating our theoretical aims back towards the practices of the field of logic and suitably diverging from the traditional approach in terms of its methodology and scope of inquiry.…”
Section: The Motivation For Plpmentioning
confidence: 99%
“…Given that various such competing logics are still advocated in the literature, some (Resnik 1999) have concluded that the persistent disagreement between candidate theories in the field is evidence that logic is more akin to ethics than to the sciences. This, however, neglects the significant ways in which logicians as participants in the debates agree, such as on how logics should be evaluated (relative to a purpose), the relative strengths and weaknesses of the various competing theories, and what would constitute sufficient evidence for the resolution of the debate (Martin 2021b) What results is a picture of theory evaluation and debate more similar to the sciences than to ethics (Martin and Hjortland 2021). 7 PLP's positive proposal is to address these shortcomings of traditional philosophy of logic through a combination of re-orientating our theoretical aims back towards the practices of the field of logic and suitably diverging from the traditional approach in terms of its methodology and scope of inquiry.…”
Section: The Motivation For Plpmentioning
confidence: 99%
“…We find advocates of competing logics debating with one another not only over the comparative strengths and weaknesses of their candidates but also over the validity of important logical laws, such as modus ponens (Martin and Hjortland 2021). While for advocates of a practice‐based approach this clash with logical practice spells a devastating blow to constitutivism , the constitutivists themselves seem content to admit that those who challenge the logical laws putatively constitutive of rational thought cannot be providing rational considerations (Martin 2021b), even if these challenges are taken seriously by their peers.…”
Section: Benefit 1: Progress On Established Questionsmentioning
confidence: 99%
“…Desde la publicación de The Logic of Deep Disagreements (Fogelin 2005(Fogelin [1985), los desacuerdos profundos han sido un tema que ha atraído mucha atención en la filosofía analítica, sobre todo en epistemología (Feldman 2005;Godden & Brenner 2010;Lynch 2010Lynch , 2016Kappel 2012), pero también en campos como la lógica (Martin 2019), la ética (Enoch 2009), la filosofía de la ciencia (De Cruz & De Smedt 2013) o la política (Fuentes-Bravo & Lavín 2014). De acuerdo con Robert Fogelin, en un desacuerdo profundo no existe acuerdo entre las partes respecto a las creencias y principios que subyacen al desacuerdo.…”
Section: Introductionunclassified